Lower Habitat Quality Increases Physiological Stress in an Endangered Neotropical Primate - Kaisin, Olivier [UNESP]; Amaral, Rodrigo Gonçalves [UNESP]; Bufalo, Felipe [UNESP]; Sabino, Gabriel Pavan; Palme, Rupert; Poncin, Pascal; Rezende, Gabriela Cabral; Brotcorne, Fany; Culot, Laurence [UNESP] (Wiley, 2025)
Understanding how habitat quality affects wildlife is one of the fundamental questions of conservation biology and ecology. Across the tropics, habitat loss and degradation threaten arboreal species, such as primates. To establish well-founded, species-specific conservation management plans, it is crucial to have an adequate understanding of a species' diet, behaviour, habitat, ecology and physiology. Measuring physiological stress in these species offers exclusive insight into how they cope and adapt within their environment. Here, we evaluated the influence of habitat quality on cortisol levels in black lion tamarins (Leontopithecus chrysopygus), an endangered frugivorous–faunivorous primate endemic to the state of São Paulo, Brazil. We compared hair cortisol concentrations among six different black lion tamarin populations inhabiting forest fragments of varying quality. We adopted a patch-landscape approach and measured forest cover to estimate habitat availability for each population. To estimate forest quality in each study, we calculated total tree basal area, a proxy for forest structure and maturity that is positively correlated to fruit availability. Our model revealed that cortisol levels increased as the amount of available habitat and tree basal area decreased. Lower forest cover may alter resource acquisition and disrupt ranging patterns of black lion tamarins, as well as increase the degree of anthropogenic disturbances. Furthermore, forests with smaller trees might impair their movement and decrease fruit and sleeping site availability. Given that small, unprotected fragments and riparian forests represent important habitats in its geographic range, protecting such areas, while increasing inter-fragment connectivity and limiting human encroachment, is crucial for the conservation of this species.
Keywords: black lion tamarins; glucocorticoids; habitat fragmentation; habitat loss; hair cortisol; Leontopithecus chrysopygus; physiological stress; primate